Mitofusins Mfn1 and Mfn2 are required to preserve glucose-but not incretin- stimulated beta cell connectivity and insulin secretion - Georgiadou,E; Muralidharan,C; Martinez,M; Chabosseau,P; Tomas,A; Su,Wern FY; Akalestou,E; Stylianides,T; Wretlind,A; Legido-Quigley,C; Jones,B; Noriega,LL; et al. (bioRxiv, 2021)
Aims/hypothesis Mitochondrial glucose metabolism is essential for stimulated insulin release from pancreatic beta cells. Whether mitochondrial networks may be important for glucose or incretin sensing has yet to be determined.Methods Here, we generated mice with beta cell-selective, adult-restricted deletion of the mitofusin genes Mfn1 and Mfn2 (βMfn1/2 dKO). Whole or dissociated pancreatic islets were used for live beta cell fluorescence imaging of cytosolic or mitochondrial Ca2+ concentration and ATP production or GSIS in response to increasing glucose concentrations or GLP-1 receptor agonists. Serum and blood samples were collected to examine oral and i.p. glucose tolerance.Results βMfn1/2 dKO mice displayed elevated fed and fasted glycaemia (p<0.01, p<0.001) and a >five-fold decrease (p<0.0001) in plasma insulin. Mitochondrial length, glucose-induced polarisation, ATP synthesis and cytosolic Ca2+ increases were all reduced (p<0.05,p<0.01,p<0.0001) in dKO islets, and beta cell Ca2+ dynamics were suppressed in vivo (p<0.001). In contrast, oral glucose tolerance was near normal in βMfn1/2 dKO mice (p<0.05, p<0.01) and GLP-1 or GIP receptor agonists largely corrected defective GSIS from isolated islets through an EPAC-dependent signalling activation.Conclusions/interpretation Mitochondrial fusion and fission cycles are thus essential in the beta cell to maintain normal glucose, but not incretin, sensing. Defects in these cycles in some forms of diabetes might therefore provide opportunities for novel incretin-based or other therapies.Impact of Mfn1/2 deletion on glucose and incretin stimulated-insulin secretion in beta cells. (A) In control animals, glucose is taken up by beta cells through GLUT2 and metabolised by mitochondria (elongated structure) through the citrate (TCA) cycle, leading to an increased mitochondrial proton motive force (hyperpolarised Δψm), accelerated